Guyana. Significant achievements 2011 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Guyana during 2011 are identified, with respect to the needs and interests of the country, strengthening issues such as innovation, production, health and safety, good agricultural practices, standards, aquaculture, agribusiness, training, beekeeping. , rural development, plant health, greenhouses, and hydroponics. Finally, technical assistance was provided in the inclusion of young people and women, pest control, such as the starfruit fruit fly, and in the value chains of vegetables and fruits.